Two-dimensional conductive covalent organic framework for efficient electrocatalytic nitrogen reduction reaction. (April 2023) - Zhang, Ning; Wang, Mei-Yan; Liu, Jing-Yao
Abstract: Electrochemical N2 reduction to NH3 is a promising green and environmentally friendly to the Haber-Bosch process. Two-dimensional covalent organic framework (COF) materials have broad application prospects in the field of catalysis due to their high stability and abundant active sites. Here, based on the structure of Co-based COF synthesized in previous experiments, six potential metal-based COFs (TM-COF, M = Nb, Mo, Co, Hf, Ta, W) catalysts were designed for electrocatalytic N2 reduction reaction (NRR). Using the density functional theory, the detailed calculation of the reaction pathway of the selected Nb-, Mo- and Ta-COF candidates was carried out. The results showed that NRR occurred through the consecutive, distal and mixed mechanisms on Nb-, Mo- and Ta-COF, respectively. Three TM-COF materials exhibit good NRR catalytic activity and high selectivity toward NH3 . Among them, Nb-COF has the best catalytic activity with a limiting potential of only −0.02 V. In addition, the calculations verified that these three TM-COFs have good thermodynamic, dynamic and electrochemical stability. Therefore, Nb-, Mo-, Ta-COF predicted in this study are expected to be synthesized in experiments and are potential efficient electrocatalysts for N2 reduction. Graphical abstract: Image 1 Highlights: Metal-based covalent organic frameworks are used as promising NRR catalysts. Three selected (TM-COF, TM = Nb, Mo, Ta) show good catalytic performance. Nb-COF has excellent catalytic activity with the U L of −0.02 V.